Revisiting the Role of Vouchers and Charter Schools in the Educational Market Place - Scott R. Sweetland (Educational Considerations, 2014)
Perspectives on Vouchers and Charter Schools. Vouchers and charter schools are among the most recognized buzzwords in today’s education marketplace. Advocates assert that the quality of education will improve if consumers (i.e., parents) have greater access to schooling alternatives.
Keywords: charter schools; education; vouchers; regulations; entrepreneurial; communications; enrollment; growth; marketplace; Parental Choice Program